Deciphering CO2 flux and fluorescent DOM origins in the carbon cycle of Kaptai Lake - Osman Miah; Rhidi Barma; Md. Anamul Hassan; Mashura Shammi; Shafi M. Tareq (PLoS ONE, 2025)
This study aimed to assess the current water quality, identify the sources of fluorescent dissolved organic matter (fDOM), and quantify the CO 2 flux from Kaptai Lake surface water. A water quality multiparameter analyzer, a membrane-enclosed pCO 2 sensor, and a weather monitoring device were deployed to continuously record data over 48 hours to observe daily and spatial shifts. All measured water quality parameters remained within the acceptable limits set by the Department of Environment (DoE). The three-dimensional excitation-emission matrix (3D-EEM) analysis identified distinct fluorophores at peak A (Ex/Em = 245/404 nm), peak M (Ex/Em = 310/404 nm), peak T (Ex/Em = 280/338–346 nm), and peak Tuv (Ex/Em = 230/338–350 nm). Parallel factor analysis (PARAFAC) modelling further resolved these into protein-like components and fulvic-like substances, specifically C-like and M-like fluorophores, indicating the presence of both microbial and terrestrial sources. Spatial distribution patterns of fDOM intensity suggest variability driven by localized pollution sources across the lake. Optical indices further indicated that the fDOM components were predominantly biologically derived, characterized by low aromaticity, lower molecular weight and size, and were largely influenced by microbial degradation processes. Diurnal monitoring of partial pressure of CO 2 (pCO 2 ) in the lake water revealed values ranging from 577 to 1045 µatm. Correspondingly, the CO 2 flux (FCO 2 ) varied between 45 and 56 mmol CO 2 m ⁻ 2 d ⁻ 1 . The positive average FCO₂ indicates that the lake acts as a net source of CO 2 to the regional atmosphere. Higher pCO 2 levels are linked to lower dissolved oxygen and increased protein-like DOM that fuels microbial respiration, while humic-like DOM helps stabilize carbon by limiting CO 2 release.